Transcranial magnetic stimulation in the treatment of phantom limb pain: a systematic review - Gabriel Rocha Santos Knorst; Phamella Rocha de Souza; Armani Gontijo Plácido Di Araújo; Samantha Avanço Ferraz Knorst; Denise Sisterolli Diniz; Hélio Fernandes da Silva Filho (Arquivos de Neuro-Psiquiatria)
Background Phantom limb pain (PLP) occurs after amputations and can persist in a chronic and debilitating way. Repetitive transcranial magnetic stimulation (rTMS) is a non-invasive neuromodulation method capable of influencing brain function and modulating cortical excitability. Its effectiveness in treating chronic pain is promising.